2018
DOI: 10.4025/actascihealthsci.v40i1.33655
|View full text |Cite
|
Sign up to set email alerts
|

<b>Correlation between flexibility and muscular power in vertical jumps in women practitioners handball and weight lifters

Abstract: The present study has the objective to correlate the variables of flexibility and muscle power present in the vertical jumps, through tests done with female individuals, performing analyzes about two groups: Handball players (HG); weight lifters (WL). Initially, the protocol consisted on the performing of the flexibility test at Wells Bank. Subsequently, the jump test was performed, using the Counter movement jump (CMJ) and Squat jump (SJ). About the study groups, it can be observed that they have similar phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…It means that leg muscle power variables and leg flexibility as independent variables have a contribution of 24.50% to kedeng smash ability as a dependent variable. The jumping tests have shown correlation between variables of flexibility and power in handball athletes [13]. The results from the field study showed that the combination of leg muscle explosive power (X1) and flexibility (X2) have significant contributions to lay-up shoot skills (Y).…”
Section: Resultsmentioning
confidence: 99%
“…It means that leg muscle power variables and leg flexibility as independent variables have a contribution of 24.50% to kedeng smash ability as a dependent variable. The jumping tests have shown correlation between variables of flexibility and power in handball athletes [13]. The results from the field study showed that the combination of leg muscle explosive power (X1) and flexibility (X2) have significant contributions to lay-up shoot skills (Y).…”
Section: Resultsmentioning
confidence: 99%
“…Os saltos verticais são amplamente utilizados quando se tem o objetivo de avaliar o desempenho funcional dos membros inferiores (Barbosa et al, 2018). Com frequência o SJ e o CMJ são conjuntamente listados nos estudos por permitirem analisar o desempenho sob a perspectiva de um recrutamento muscular puramente concêntrico no SJ e avaliar a influência de um benefício do componente muscular elástico produzido no ciclo alongamento-encurtamento resultante das contrações excêntrica e concêntrica em sequência durante o CMJ (Lima, 2022).…”
Section: Squat Jump (Sj) E Counter Movement Jump (Cmj)unclassified